Analisis pengaruh ekspor ke China terhadap tingkat pengangguran di dua Negara di Kawasan Selat Malaka (Indonesia dan Malaysia) - Zamzami, Zamzami; Mustika, Candra (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims to analyze the development of Indonesian and Malaysian exports to China and the level of unemployment in both countries during the period 1993 to 2014 and analyze the effect of exports to China on the unemployment rate in both countries, namely Indonesia and Malaysia the development of the value of Indonesian exports to China. The results of the study showed that during the period 1993-2014 there were fluctuations from year to year with an average development rate over the period of 15.30% while the average export value during the period was 8,047.22 Million US dollars, the unemployment rate in Indonesia during the period 1993 - 2014 fluctuated or an increased and decrease with an average growth rate of 7.97%. The regression results of the panel data model show that the value of exports to China does not significantly influence the number of unemployed people in Indonesia and Malaysia.